2019
DOI: 10.1186/s12978-019-0740-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of maternal smoking prior to and during pregnancy in a regional Danish population: a cross-sectional study

Abstract: Background Maternal smoking is still a major public health problem posing the risk of several negative health outcomes for both the pregnant woman and her offspring. The prevalence of maternal smoking in Denmark and other high-income countries has decreased continuously since the 1980s, and a prevalence below 10% of women who continue to smoke during pregnancy has been reported in studies after 2010. Previous studies have shown that low socioeconomic status is associated with maternal smoking. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 39 publications
7
45
2
Order By: Relevance
“…In the current study, findings concerning working status, even though not significant, align with those in the literature, that report occupation as a predictor for smoking before and during pregnancy 11,13,26 ; occupation is also commonly related to an individual education and income 44 . Research also supports that smoking is a habituated response to the circumstance of housewife, often associated with economic vulnerability 45 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the current study, findings concerning working status, even though not significant, align with those in the literature, that report occupation as a predictor for smoking before and during pregnancy 11,13,26 ; occupation is also commonly related to an individual education and income 44 . Research also supports that smoking is a habituated response to the circumstance of housewife, often associated with economic vulnerability 45 .…”
Section: Discussionsupporting
confidence: 89%
“…As reported by other authors 11,13,22 , in our study, educational disadvantage was found to be a predictor of smoking status during pregnancy; participants who belong to the highest educational levels had a lower probability of smoking. In Portugal, these inequalities in pregnant smoking women have also been previously described 16 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A recent study highlighted the correlation between higher tobacco store density and lower socioeconomic status with higher smoking-during-pregnancy rates [ 13 ]. Another study found predictors of maternal smoking during pregnancy related to women from lower socioeconomic backgrounds; these included unemployment, less time in education and women living alone [ 14 ]. Barriers related to psychological well-being were also identified as being highly influential; for example, women can perceive the stress related to a quit attempt to be more detrimental to their mental health and the health of the baby than continued smoking [ 12 ].…”
Section: Introductionmentioning
confidence: 99%